Assessment of concentrations of iron and zinc and bioavailable iron in grains of earlymaturing tropical maize varieties - Oikeh, S.O.; Menkir, A.; Maziya-Dixon, B.B.; Welch, R.; Glahn, Raymond P. (American Chemical Society, 2003)
Twenty elite early-maturing (75−90 days) tropical maize varieties grown in three diverse agroecologies in West Africa were evaluated to identify varieties with high kernel-Fe and -Zn and bioavailable Fe levels. Bioavailable iron was assessed using an in vitro digestion/Caco-2 cell model. Significant (P < 0.001) varietal differences were observed in mean kernel-Fe and -Zn levels. The ranges were 15.5−19.1 mg kg-1 for Fe and 16.5−20.5 mg kg-1 for Zn. Genetic component accounted for 34% of the total variation in kernel-Zn and for 11% of the variation in kernel-Fe levels. Mean bioavailable Fe in varieties ranged between 4% below and 49% above the reference control variety. A significant negative relationship was detected between kernel-P concentration and bioavailable Fe (R = −0.36; P < 0.004; n = 60). Two varieties, ACR90POOL16-DT and ACR86TZESR-W, were identified as the most promising for further evaluation to determine their efficacy as improved sources of iron in target populations.